PCs all-in-one for dummies - Chambers, Mark L. (Laura Ann); 1906-1998.; 1970- (Hoboken, NJ John Wiley & Sons, 2013)
A perfect companion for your desktop PC! Whether you use your PC for work or play, there's a lot to learn and a lot of territory to discover, so take along a good guide -- |c Source other than Library of Congress.
Previous edition: 2010. Includes index.
Keywords: Microcomputers; Microcomputers -- Handbooks, manuals, etc; Internet; Computer networks; Microsoft Windows (Computer file); Microsoft Office; Microsoft Word; Microsoft Outlook; Microsoft PowerPoint (Computer file); Microsoft Excel (Computer file)